Citizen Science in Europe: challenges in conducting citizen science activities in cooperation with university and public libraries (PUBMET, 2022)
Citizen science (CS) has many definitions but is commonly known as collaboration between professional scientists and the rest of society (Ignat et al., 2018). Although there have been cases of its implementation in the past, the term became globally known in 2012 (Vohland et al., 2021). CS activities involve a wide range of academic disciplines and vary widely in what is required of participants in terms of knowledge, time commitment, travel, and use of technology (Cohen et al., 2015).For the past ten years, academic, public, and research libraries have often supported and conducted CS to encourage greater interaction between science and society. Each of these library types has a specific user population; academic libraries have students and scientific and teaching staff, public libraries have local community, and research libraries have researchers. However, they seldom cooperate. Some collaboration challenges are owed to its complexity, uncertainty regarding research co-creation, and participant retention strategies (Cigarini et al., 2021), and its aspects have been explored by the LIBER project CeOS_SE Project - Citizen-Enhanced Open Science in Southeastern Europe Higher Education Knowledge Hubs (more information on https://libereurope.eu/project/ceos_se-project-citizenenhanced-open-science-in-southeastern-europe-higher-education-knowledge-hubs/). The main goal of the project is to raise awareness of mainstream open science and CS practices in Southeastern (SE) Europe. As a project partner, the National and University Library in Zagreb, in cooperation with the University Library of Southern Denmark, conducted a survey that included other European countries in addition to SE Europe to examine and collect good practices of civil engagement in university libraries. The survey was sent across the European university libraries with the help of other project partners (libraries from Netherlands, Italy, Greece, Cyprus, Serbia, and Bulgaria). The survey also investigated whether university libraries carried out CS activities in collaboration with public libraries and if not, why. A relatively small number of university libraries declared that they cooperated with public libraries in creating CS activities. Those that did were interviewed to see which challenges they faced and how they solved them.Here we will present the main challenges, barriers, and difficulties that stand in the way of cooperation between university and public libraries in Europe. We will also try to explain the reasons for relatively modest cooperation in CS activities and suggest possible solutions from which both university and public libraries could benefit. Co-created activities modify the relationship between libraries and librarians but also with their users, shifting it towards a more participatory interaction (Cigarini et al., 2021).
Keywords: books; monographs; open access; peer review